INFLUENCE OF THERMAL RADIATION ON FOREST SOILS - Voron, V. P.; Borysenko, V. H.; Barabash, I. O.; Muntian, V. K.; Tkach, O. M.; Sydorenko, S. H.; Melnyk, Ye. Ye. (Forestry and Forest Melioration, 2018)
Introduction Forest fires are a powerful environmental factor that breaks the balance between the individual components of forest ecosystems. One of the types of heat distribution during surface fires in forests is thermal radiation. Considerable effort has been devoted to studying the impact of fire on forest stands. Much less information is available on the influence of fire thermal radiation on soils. Therefore, it is important to assess both the thermal regimes of the fire affecting the surface layer of the soil and the vital functions of the root system of plants. The aim of the study was to determine the parameters and changes in the temperature conditions of forest soils under the influence of the heat radiation that is nearly identical to heat radiation during forest fires. Materials and Methods The objects of the study were the following weak sod soils: the sandy soil from the pure pine stand and the gray forest soil from the oak stand. The research methodology was developed by V. P. Voron, V. K. Muntian, V. H. Borysenko and I. O. Barabash. Four experiments were carried out: two soil monoliths were collected in pine stands and two ones in oak stands. In each type of soil two options were investigated, moist and dry. The monoliths of the soils were radiated with heat in specially created laboratory equipment. The facility allows detecting heat flux distribution in soils under laboratory conditions. For measuring the temperature in the soil monoliths, thermocouples were mounted and fixed. The thermal elements were connected to the computer via an analog-to-digital converter (ADC). The signal from the ADC was processed by the OWEN Process Manager software. During the simulation of the soil heating regime, we used the temperature values detected by previous studies when the bottom layer of the litter was combusted; in the earlier studies, the burning temperature varied from 200 to 350°C. Results Depending on the type of the soil, all cases were divided into two variants: moist and dry. The temperature of the moist samples was much lower. In the weak sandy soil, the surface temperature of the dry sample was 70°C higher than of the moist one (378°C against 304°C). This difference for gray forest soil was even more significant, 200°C. Under the heating, the dry weak sandy soil reached a higher temperature deeper into the profile than the moist one. If in the dry soil the temperature reached 186°C at a depth of 4 cm then in the moist sample it was only 76°C. Similarly, at a depth of 6 cm, the temperature was 120°C in dry sample and 67°C in the moist one. This trend was not so pronounced in the gray forest soil. Sandy soil warmed up deeper and to higher temperatures than loamy soil did. For example, at a depth of 10 cm, the temperature was 63–67°C in sandy soil and 42–49°C in loam. Conclusions Soil heating has a pronounced surface nature. The highest temperature was observed on the surface of the soil. As the depth increased the temperature dropped. The most noticeable decrease was observed in a surface layer from 0 to 4 cm. The growth of temperatures in the depth of the monoliths was observed with a certain delay, even after stopping the heat radiation. The heating of dry sandy soils deep into the profile occurs more strongly than in the moist sample. The causes of this could be their lower porosity and greater mineralization. The sandy soil was found to warm deeper and more intensively as compared to the loamy soil. 7 Figs., 20 Refs.